MEMBANGUN INTERAKSI HUMANISTIK DALAM PROSES PEMBELAJARAN - Takrifin, Ahmad (Forum Tarbiyah, 2009)
Humanictic learning interaction is a must to be built. This is because, at present, our education authoritarianism puts forward in the learning process. Authoritarianism is realized in the form of oriented teacher / teacher-centric, which places the teacher as a learning center and the only source of knowledge, on the contrary, like a piggy bank to place students who are ready to be saved by his teacher. This is the so-called multicultural education leading experts from Brazil, Paulo Freire, as an educational “bank style” (banking system). The learning process is thus make participants into the humans who had lost the power of humanity (dehumanism). Building a humanistic interaction in the learning process should be started from both parties (teacher – disciple ). There is no more on the pattern of authoritarian, top-down coercion, and oppression of learners. What will appear in these interactions is the awareness of teachers and students for dialogue, partnership, joint problems, and so forth. When this is done, then our learners will be the perfect human being innovative, creative, reliable, independent and humane.